Antibody-drug conjugates targeting HER2 for the treatment of urothelial carcinoma: potential therapies for HER2-positive urothelial carcinoma - Shih, Chia-Hsien; Lin, Yu-Hua; Luo, Hao-Lun; Sung, Wen-Wei (Frontiers in Pharmacology, 2024)
Urothelial carcinoma (UC) is a common cancer characterized by high morbidity and mortality rates. Despite advancements in treatment, challenges such as recurrence and low response rates persist. Antibody-drug conjugates (ADCs) have emerged as a promising therapeutic approach for various cancers, although their application in UC is currently limited. This review focuses on recent research regarding ADCs designed to treat UC by targeting human epidermal growth factor receptor 2 (HER2), a surface antigen expressed on tumor cells. ADCs comprise three main components: an antibody, a linker, and a cytotoxic payload. The antibody selectively binds to tumor cell surface antigens, facilitating targeted delivery of the cytotoxic drug, while linkers play a crucial role in ensuring stability and controlled release of the payload. Cleavable linkers release the drug within tumor cells, while non-cleavable linkers ensure stability during circulation. The cytotoxic payload exerts its antitumor effect by disrupting cellular pathways. HER2 is commonly overexpressed in UCs, making it a potential therapeutic target. Several ADCs targeting HER2 have been approved for cancer treatment, but their use in UC is still being tested. Numerous HER2 ADCs have demonstrated significant growth inhibition and induction of apoptosis in translational models of HER2-overexpressing bladder cancer. Ongoing clinical trials are assessing the efficacy and safety of ADCs targeting HER2 in UC, with the aim of determining tumor response and the potential of ADCs as a treatment option for UC patients. The development of effective therapies with improved response rates and long-term effectiveness is crucial for advanced and metastatic UC. ADCs targeting HER2 show promise in this regard and merit further investigation for UC treatment.